TERT promoter C228T mutation in neural progenitors confers growth advantage following telomere shortening in vivo. Issue 12 (23rd March 2022) - Miki, Shunichiro; Koga, Tomoyuki; Mckinney, Andrew M; Parisian, Alison D; Tadokoro, Takahiro; Vadla, Raghavendra; Marsala, Martin; Hevner, Robert F; Costello, Joseph F; Furnari, Frank
Abstract: Background: Heterozygous TERT (telomerase reverse transcriptase) promoter mutations (TPMs) facilitate TERT expression and are the most frequent mutation in glioblastoma (GBM). A recent analysis revealed this mutation is one of the earliest events in gliomagenesis. However, no appropriate human models have been engineered to study the role of this mutation in the initiation of these tumors. Method: We established GBM models by introducing the heterozygous TPM in human induced pluripotent stem cells (hiPSCs) using a two-step targeting approach in the context of GBM genetic alterations, CDKN2A/B and PTEN deletion, and EGFRvIII overexpression. The impact of the mutation was evaluated through the in vivo passage and in vitro experiment and analysis. Results: Orthotopic injection of neuronal precursor cells (NPCs) derived from hiPSCs with the TPM into immunodeficient mice did not enhance tumorigenesis compared to TERT promoter wild type NPCs at initial in vivo passage presumably due to relatively long telomeres. However, the mutation recruited GA-Binding Protein and engendered low-level TERT expression resulting in enhanced tumorigenesis and maintenance of short telomeres upon secondary passage as observed in human GBM. These results provide the first insights regarding increased tumorigenesis upon introducing a TPM compared to isogenic controls without TPMs. Conclusion: Our novel GBM models presented the growth advantage of heterozygous TPMs for the first time in the context of GBM driver mutations relative to isogenic controls, thereby allowing for the identification and validation of TERT promoter-specific vulnerabilities in a genetically accurate background.